Pengaruh Penggunaan Modul Cerdas Siswa (Mcs) PAI Terhadap Hasil Belajar Siswa Kelas IX Di SMP 1 Karawang Barat - Awaliah, Dede Siti; Sitika, Achmad Junaedi; Nurhasan, Nurhasan (Peneliti.net, 2023)
This study aims to determine the effect of the use of the Modul Cerdas Siswa (MCS) PAI on student learning outcomes. This type of research is an experimental method (Quasy Experiment), with a non-equivalent control group design. The population taken is class IX even semester 2022/2023 SMPN 1 West Karawang. The sampling technique used purposive sampling. The samples taken were class IX B as an experimental class of 35 students and class IX C as a control class as well as 35 students. The data collection instrument used a test (pretest-posttest). The results of this study indicate that there are differences in the average student learning outcomes of the experimental class and the control class. the average student learning outcomes of the experimental class was 84.57 and the average value of the control class student learning outcomes was 63.29. This is proven by the significant value on the t test (independent sample test) which is less than 0.05, namely Sig. (2-tailed) 0.000 <0.05, thus H0 is rejected and Ha is accepted, which means that there is an effect of the use of the Modul Cerdas Siswa (MCS) PAI on the learning outcomes of class IX students at SMPN 1 Karawang Barat.